The Integrative Role And Capacity Of The Banking Sector In Uzbekistan - Suleymanov Ilnur Radikovich (Academia One Publishing, 2025)
This article examines the integrative potential of the banking sector in the Republic of Uzbekistan within the context of national economic development. Through an analysis of macroeconomic indicators, structural reforms, and financial metrics from 2020 to 2024, the study evaluates the sector's capacity to support the real economy, promote financial stability, and enhance investment activities. Special attention is given to the synergy between the banking and industrial sectors, the digitalization of banking services, and the sector’s adaptation to global financial challenges
Keywords: Uzbekistan; banking sector; economic integration